Heart rate variability during exertional heat stress: effects of heat production and treatment - Flouris, A. D.; Bravi, A.; Wright-Beatty, H. E.; Green, G.; Seely, A. J.; Kenny, G. P. (European Journal of Applied Physiology, 2014)
Purpose We assessed the efficacy of different treatments (i.e., treatment with ice water immersion vs. natural recovery) and the effect of exercise intensities (i.e., low vs. high) for restoring heart rate variability (HRV) indices during recovery from exertional heat stress (EHS). Methods Nine healthy adults (26 ± 3 years, 174.2 ± 3.8 cm, 74.6 ± 4.3 kg, 17.9 ± 2.8 % body fat, 57 ± 2 mL·kg·-1 min-1 peak oxygen uptake) completed four EHS sessions incorporating either walking (4.0-4.5 km·h-1, 2 % incline) or jogging (~7.0 km·h-1, 2 % incline) on a treadmill in a hot-dry environment (40 °C, 20-30 % relative humidity) while wearing a non-permeable rain poncho for a slow or fast rate of rectal temperature (T re) increase, respectively. Upon reaching a T re of 39.5 °C, participants recovered until T re returned to 38 °C either passively or with whole-body immersion in 2 °C water. A comprehensive panel of 93 HRV measures were computed from the time, frequency, time-frequency, scale-invariant, entropy and non-linear domains. Results Exertional heat stress significantly affected 60/93 HRV measures analysed. Analyses during recovery demonstrated that there were no significant differences between HRV measures that had been influenced by EHS at the end of passive recovery vs. whole-body cooling treatment (p > 0.05). Nevertheless, the cooling treatment required statistically significantly less time to reduce T re (p < 0.001). Conclusions While EHS has a marked effect on autonomic nervous system modulation and whole-body immersion in 2 °C water results in faster cooling, there were no observed differences in restoration of autonomic heart rate modulation as measured by HRV indices with whole-body cold-water immersion compared to passive recovery in thermoneutral conditions.